Role of thrombophilia screening in recurrent pregnancy loss and poor pregnancy outcome - V., Divya; N., Sumathi; Poomarimuthu, Mahesh Kumar; Govindan, Ramajayam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The pathophysiology of recurrent pregnancy loss is poorly understood and some factors have been implicated as causes of RPL including genetics, metabolic and infections. But still in majority of RPL cases, cause remains unexplained (around 40-50%). Recent few studies have shown that there is significant association between thrombophilia and RPL. The genetic predisposition to venous thrombosis such as factor V Leiden, factor V HR2 haplotype, factor V HongKong/Cambridge and PAI-1 4G/5G promoter polymorphism have been reported to be associated with RPL. This study examined the specific prevalence of genetic thrombophilic markers in women with recurrent miscarriage. Methods: A retrospective case-control study designed with 50 RPL cases and 50 healthy controls. Genotyping of the four thrompohilic mutation were performed by PCR-RFLP and AS-PCR methods. Results: The frequencies of factor V HR2 haplotype mutant heterozygous form (OR=1.46; p=0.758), PAI-1-675 4G/4G (OR=1.13; p=0.806) and PAI-1 -675 5G/5G (OR=1.24; p=0.815) were moderately higher in RPL patients than controls. While, the mutant form of factor V Hong Kong and factor V Cambridge were completely absent in this study population. Conclusions: To our best knowledge, this is the first study to investigate the association of Factor V HR2 haplotype, factor V Hong Kong/Cambridge and PAI-1 (-675 4G/5G) mutations with RPL in South Indian population. However, this study did not reveal any significant association between studied mutations and RPL due to small sample size.